Symbols and meanings of kanji with bushu onnahen As representation of women - Sunarni, Nani (Japanese Research on Linguistics, Literature, and Culture, 2021)
Kanji are characters used in Japanese which are the result of Chinese thought adopted by Japanese society. The main elements in kanji (bushu) can be gender markers, water, trees, and others. One of these elements is a female gender symbol called onnahen. The data used in this study, in the form of kanji with bushu onnahen. The data were analyzed based on the theory of semiotics and hypersemiotics which view kanji as a cultural phenomenon. The results of the analysis identified that the female symbol in the kanji with bushu onnahen represents that Japanese woman have a respectable character when they become a wife and mother, are authoritative, trustworthy, helpful, but have no character, are false, selfish, and jealous. Theoretically, this research is useful to add references in the study of gender and kanji.